De Novo Biosynthesis of Apigenin, Luteolin, and Eriodictyol in the Actinomycete Streptomyces albus and Production Improvement by Feeding and Spore Conditioning - Marín, Laura; Gutiérrez-del-Río, Ignacio; Yagüe, Paula; Manteca, Ángel; Villar, Claudio J.; Lombó, Felipe (Frontiers in Microbiology, 2017)
Nutraceutical compounds as plant flavonoids play an important role in prevention and modulation of diverse heath conditions, as they exert interesting antifungal, antibacterial, antioxidant and antitumor effects. They also possess anti-inflammatory activities in arthritis, cardiovascular disease or neurological diseases, as well as modulatory effects on the CYP450 activity on diverse drugs. Most flavonoids are bioactive molecules of plant origin, but their industrial production is sometimes hindered due to reasons as low concentration in the plant tissues, presence in only some species or as a complex mixture or inactive glycosides in plant vacuolae. In this work, we describe the de novo biosynthesis of two important flavones, apigenin and luteolin, and one known flavanone, eriodictyol. Their plant biosynthetic pathways have been reconstructed for heterologous expression in Streptomyces albus, an actinomycete bacterium manageable at industrial production level. Also, production levels for apigenin have been improved by feeding with naringenin precursor, and timing for settlement of secondary metabolism has been advanced by spore conditioning. In the cases of eriodictyol and luteolin, their production in this important type of biotechnology-prone bacteria, the actinomycetes, had not been described in the literature yet.